Endovascular recanalization of symptomatic chronic cerebral artery occlusion: predictors for successful recanalization and perioperative complications - Zhang, Xueqian; Li, Yang; Yin, Kuochang; Hao, Zhiwei; Fu, Yidian; Yang, Qishuo; Xu, Guodong; Lv, Peiyuan (Frontiers in Neurology, 2025)
Background and purposeEndovascular recanalization and stenting has been used to treat patients with symptomatic chronic cerebral artery occlusion, including intracranial vertebrobasilar artery occlusion and internal carotid artery occlusion. Our challenge is to improve success rates and reduce the incidence of postoperative complications. This study sought to identify potential predictors for successful recanalization.MethodsOur study included 103 consecutive patients between February 2021 and October 2024 with symptomatic chronic cerebral artery occlusion who were treated with endovascular recanalization. We recorded clinical information, laboratory and examination results, radiologic characteristics and procedural results of patients. Factors affecting surgical outcomes were analyzed by univariate and multivariate analyses.ResultsA total of 103 consecutive CCAO recanalization attempts were performed from February 2021 to October 2024 in 103 patients (78 men; age 61.1 ± 11.1 years; range: 32–81 years) with overall technical success rate 68.9%. Patients had chronic comorbidities such as hypertension (78, 75.7%), diabetes mellitus (32, 31.10%), and cardiac disease (12, 11.7%). 38 (36.9%) had a history of smoking, and 23 (22.3%) had a history of drinking. The rate of overall intraoperative complication was 10.7% (11/103). Multivariate analysis showed that stump morphology, smoking history, duration from last neurologic event (longer than 6 months or not), age, NLR were significantly associated with successful recanalization. According to the coefficients of the prediction model, the technical success rates were 100, 66.7 and 11.1% in patients with ≤6, 6–10, ≥10 points, respectively.ConclusionThe morphology of occluded stumps, duration from last neurologic event, age, smoking history and NLR can be used to predict the outcome of vascular recanalization.